ANGGOTA TUBUH TERKHITBAH YANG BOLEH DI PANDANG MENURUT IBNU HAZM - Rasyidin, Muhammad Alwin Abdillah, (IAIN LANGSA, 2019)
To reach an ideal household (mawaddah warohmah), various preparatory efforts areneeded as early as possible to support the marriage. This preparation must have started since theintroduction process until there is a determination to get to the marriage level. Broadly speaking,preparations that must be required include a prospective husband and wife must be ready ormature physically, mentally (psychologically), socially and sexually. Khitbah in Indonesian isthe same as engagement, engagement or proposal. The word